Feasibility of using futures contracts of the Chicago Mercantile Exchange for hedging price risk in Chilean cattle (2019)
The aim of this paper is to study the feasibility of using Chicago Mercantile Exchange futures contracts as a price risk hedging instrument for cattle in Chile. For this purpose, seasonal unit root tests were performed, and the Johnson-Stein model was used to estimate the minimum risk hedge ratios between 1975 and 2012. The results show that the cattle markets are integrated and that the optimal hedge ratio for a livestock producer is in line with the estimated ratios for other commodities. These findings can be useful for agricultural policy makers in developing countries because they confirm the potential of this type of instrument to reduce the price risk for livestock producers and provide empirical arguments to encourage its use. © 2018 Universidad de Antioquia. All rights reserved.